2009
DOI: 10.1007/s11240-009-9536-8
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal DNA amplification facilitates the identification of a broad spectrum of bacteria, fungi and protozoa in Eleutherococcus sp. plant tissue cultures

Abstract: In vitro cultures of Eleutherococcus sieboldianus originating from surface sterilized leaf explants were found to be associated with several microorganisms. The associations included bacteria, fungi and protozoa within the rhizosphere and inside root hairs. To determine if this phenomenon is unique to this species, plant tissue cultures of E. gracilistylus and E. senticosus were included in our studies for comparison. A methodology consisting of isothermal amplification, cloning and sequencing was established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
0
8
0
3
Order By: Relevance
“…Furthermore, after quality testing with a NanoDrop 2000 and 1% agarose gel electrophoresis, the samples were dyed with EB and examined under UV light (280 nm) and subsequently stored at −20 °C. The DNA solutions from the artificial infected soil samples were extracted via the CTAB method 40 with slight modifications. Briefly, each 0.1 g soil sample was carefully ground with 1 mL lysis buffer (Tris-HCl 100 mM, pH = 9.0, EDTA 100 mM, NaCl 400 mM, 2% SDS) and 0.5 g of quartz sand in a mortar.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, after quality testing with a NanoDrop 2000 and 1% agarose gel electrophoresis, the samples were dyed with EB and examined under UV light (280 nm) and subsequently stored at −20 °C. The DNA solutions from the artificial infected soil samples were extracted via the CTAB method 40 with slight modifications. Briefly, each 0.1 g soil sample was carefully ground with 1 mL lysis buffer (Tris-HCl 100 mM, pH = 9.0, EDTA 100 mM, NaCl 400 mM, 2% SDS) and 0.5 g of quartz sand in a mortar.…”
Section: Methodsmentioning
confidence: 99%
“…In order to further knowledge, future surveys should focus on yeasts, since few articles have reported yeast endophytes in cold environments (Loque et al 2010; Godinho et al 2013; Santiago et al 2016), with none having tested the effects of these fungi on host plant performance. Studies should also focus on unicellular algae and protists, which have been shown to be present in the tissues of temperate and tropical plant species (Trémouillaux‐Guiller et al 2002; Müller & Döring 2009), but the effects of which on plants at low temperatures remain poorly defined. We also recommend studies into the effects of microbial symbionts on plant cold tolerance mediated by the synthesis of secondary metabolites, such as the antibacterial compounds produced by the fungal endophyte Phoma against the ice‐nucleating bacterium Pseudomonas syringae (Moghaddam & Soltani 2014).…”
Section: Perspectives and Further Researchmentioning
confidence: 99%
“…A ocorrência de espécies de Stenotrophomonas já foi verificada em microplantas de equinácea (LATA et al, 2006), comigo-ninguém-pode (JAN et al, 2004), lavanda-do-mar (LIU; HSU; WU,. 2005) e ginseng siberiano (MULLER;DÖRING, 2009). Ao mesmo tempo estudos com espécies de Burkholderia em abacaxizeiro comprovaram a capacidade dessas bactérias em promover o crescimento vegetal durante a fase de aclimatização de microplantas (WEBER et al, 2003a, b) e aumentar a produtividade de frutos (WEBER et al, 2004), indicando que os benefícios causados pela interação entre plantas e as bactérias dos…”
Section: Discussionunclassified
“…Visando eliminar essa competição sugere-se o uso dos primers 799f (CHELIUS;TRIPLETT, 2001) e 1492R(HEUER et al, 1997) para aumentar a concentração do DNA bacteriano antes da amplificação com grampo GC(ANDREOTE;AZEVEDO;ARAÚJO, 2009). O primer 799f vem sendo utilizado com freqüência, tendo sido relatado em vários estudos recentes em comunidades bacterianas endofíticas(IDRIS et al, 2004; MÜLLER;DÖRING, 2009;.A ARISA, desenvolvida por Fisher e Tripplett (1999) é uma técnica baseada no polimorfismo do comprimento do espaço intergênico ribossomal 16S-23S rRNA; consiste no uso de primer fluorescente na amplificação por PCR do espaço intergênico entre a menor e a maior subunidade do gene rRNA (16S-23S em procarioto). Esta região pode codificar vários tRNAs dependendo da espécie e apresenta heterogeneidade em termos do comprimento e da composição da sequência(GONZÁLEZ et al 2003;RANJARD;POLY;NAZARET, 2000).…”
unclassified